LAPAROSTOMY IN THE OUTCOME OF PLANNED COMBINED OPERATIONS IN PATIENTS WITH GASTRIC CANCER - Александр Анатольевич Мартынов; Андрей Игоревич Баранов; Сергей Александрович Ярощук; Ярослав Миронович Лещишин; Татьяна Анатольевна Афонина (Медицина в Кузбассе)
Subject of research (observation). The need for patients with gastric cancer extensive combined operations in the volume of multi-organ resections is dictated by the prevalence of pathological processes and associated intra-abdominal complications. However, the percentage of complications in such surgical interventions, including those leading to fatal outcomes, reaches 60 %. One of the options that improve the results of combined operations in gastric cancer may be the formation of a laparostomy in the outcome of the primary operation.